From a Work to an "Open" Work: Research Experience - Zavialova, Olha K.; Kalashnyk, Mariya P.; Savchenko, Hanna S.; Stakhevych, Halyna A.; Smirnova, Iryna V. (International Journal of Criminology and Sociology, 2021)
The subject of this study is the concept of "open" work, proposed by U. Eco. Based on the ideas of U. Eco, the authors interpret the "open" work in several aspects: compositional, semantic, and compositional-semantic. Compositional openness emerges in aleatoric works. The tendencies to openness are found in compositions written with the use of "non-deterministic" notation. Works that are "open" in the semantic sense have encoded meanings, the decoding of which requires the involvement of contextual meanings. Compositional-semantic openness emerges in Net Art. Cognition of the specifics of "open" works required a study of the history of the traditional "closed" work, it’s becoming and evolution in a historical perspective. The concept of "work" is investigated in conjunction with the concepts of "authorship", "creativity", "musical text", "performance", "perception", etc. It was demonstrated that the meaning of these concepts substantially changes in the context of dynamic history and culture. In modern culture, these concepts have lost their usual shape and have substantially transformed due to rapid development of computer technology and the Internet.